Pengaruh Dukungan Sosial Dan Job Insecurity Terhadap Kesejahteraan Psikologis Pegawai Dinas Pekerjaan Umum Dan Penataan Ruang (Pupr) Kota Bengkulu - Dewi, Wini Sari; Kusuma, Merta (Jurnal Fokus Manajemen, 2024)
Many factors underlie the response to customer satisfaction. The objectives of Psychological well-being is not only influenced from within the individual, but can also be influenced by the individual's environment, namely Social Support and Job Insecurity. The aims of this research are (1) to determine the effect of social support on Psychological Well-being (2) to determine the effect Job Insecurity on Psychological Well-being, and (3) to determine the effect of Social Support and Job Insecurity on Psychological Well-beingThe type of research is quantitative research, conducted from December 2023 to January 2024. Respondents are employees (contract workers) of the Bengkulu City Public Works and Spatial Planning Service. Data were collected using a questionnaire and data analysis used a multiple linear regression model and processed with SPSS software.The results of the research show that social support has a positive effect on the employees psychological well-being of Bengkulu City Public Works and Spatial Planning Department, where the regression coefficient for social support is 0.737. This means that the higher the social support, the more psychological well-being will also increase. Job Insecurity has a negative effect on the psychological well-being of Bengkulu City Public Works and Spatial Planning Department employees, where the social support regression coefficient is -0.165. This means that the higher Job Insecurity, the lower the employee's psychological well-being. Social support and job insecurity together influence the employees psychological well-being. Social support and Job Insecurity contribute 55.9% in influencing the employees psychological well-being of Bengkulu City Public Works and Spatial Planning Department.